Analysis of the Effect of Income Tax and Firm Size on Capital Structure Moderated by Sales Growth - Fauzi Nurrahmawanto; Julia Safitri; Albert Gamot Malau (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to examine and analyze the effect of income tax and firm size on the capital structure of coal mining companies, whether moderated or not by sales growth. A quantitative approach was used in this study by taking samples from 13 coal mining companies listed on the Indonesia Stock Exchange in 2018–2023. Multiple linear regression analysis was used with the help of the application Jeffry’s Amazing Statistics Program (JASP). The research results show that the income tax has no significant effect on capital structure. In contrast, the firm size has a significant positive effect on the firm’s capital structure. Moreover, the sales growth is unable to moderate the correlation between these variables on the firm’s capital structure.